Suppression of hnRNP A1 binding to HK1 RNA leads to glycolytic dysfunction in Alzheimer’s disease models - Ji, Xin-Hao; Liu, Ting-Ting; Wei, Ai-Hong; Lei, Hui-Ping; Chen, Yue; Wu, Ling-Nan; Liu, Ju; Zhang, Ying; Yan, Fei; Chen, Mei-Xiang; Jin, Hai; Shi, Jing-Shan; et al. (Frontiers in Aging Neuroscience, 2023)
Objective To investigate the mechanism of RNA-binding protein hnRNP A1 in mouse hippocampal neurons (HT22) on glycolysis. Methods RIP and CLIP-qPCR were performed by HT22 in vitro to observe the mechanism of hnRNP A1 regulating the expression of key proteins in glycolysis. The RNA binding domain of hnRNP A1 protein in HT22 was inhibited by VPC-80051, and the effect of hnRNP A1 on glycolysis of HT22 was observed. Lentivirus overexpression of hnRNP A1 was used to observe the effect of overexpression of hnRNP A1 on glycolysis of Aβ25–35-injured HT22. The expression of hnRNP A1 in brain tissues of wild-type mice and triple-transgenic (APP/PS1/Tau) AD mice at different ages was studied by Western blot assay. Results The results of RIP experiment showed that hnRNP A1 and HK1 mRNA were significantly bound. The results of CLIP-qPCR showed that hnRNP A1 directly bound to the 2605-2821 region of HK1 mRNA. hnRNP A1 inhibitor can down-regulate the expression of HK1 mRNA and HK1 protein in HT22 cells. Overexpression of hnRNP A1 can significantly reduce the toxic effect of Aβ25–35 on neurons via the hnRNP A1/HK1/ pyruvate pathway. In addition, inhibition of hnRNP A1 binding to amyloid precursor protein (APP) RNA was found to increase Aβ expression, while Aβ25–35 also down-regulated hnRNP A1 expression by enhancing phosphorylation of p38 MAPK in HT22. They interact to form bidirectional regulation, further down-regulating the expression of hnRNP A1, and ultimately aggravating glycolytic dysfunction. Protein immunoblotting showed that hnRNP A1 decreased with age in mouse brain tissue, and the decrease was greater in AD mice, suggesting that the decrease of hnRNP A1 may be a predisposed factor in the pathogenesis of AD.